STRATEGI RITEL KONVENSIONAL MODERN DALAM MENGHADAPI PERSAINGAN PADA MASA PANDEMI COVID 19 - Dikdik Purwadisastra (Eqien - Jurnal Ekonomi dan Bisnis, 2021)
This study aims to determine a modern conventional retail strategy in facing competition with conventional retail. This research method is descriptive verification with a qualitative approach using SWOT analysis. Meanwhile, the author's research data sources come from questionnaires to retail consumers and interviews with retailers. The results of research using SWOT analysis show that the IFAS matrix score is 3.7 while EFAS is 3.3 which needs to improve the service system towards digital marketing in facing competition with online retail. Key word : Retail, Strategy Retail, SWOT Analysis